Fragmentação identitária no romance “O caso Morel”, de Rubem Fonseca - Angst, Carine Maria (2022)
This thesis aims to analyze identity elements in the novel O caso Morel (1995), written by Rubem Fonseca. For this, at first, some important characteristics of the historical context in which the novel was written were traced, in addition to carrying out a reflection on the social configuration at the world level and in Brazil in that period. This discussion aimed to intertwine the context of production at the time with the fragmentation of the novel and to identify possible dialogues with the period in which the text was produced. In a second moment, some considerations were made about postmodernism, a context in which the novel was produced and received by the public and critics. Thus, the theories of Jameson (1997), Lyotard (2009), Hutcheon (1991), Rouanet (1987), Bauman (2005) and Hall (2006) were chosen because it is considered that their research on postmodernity and identity converge with the fragmentary structure of the novel under study. In a third moment, the fragmentary composition of the narrators was analyzed through the narrative levels that are interspersed in the text, followed by the analysis of the social and intimate ties established, mainly, by the narrator-character of the novel. Then, it was explored how space and time are used in the narrative by the protagonists to establish links with their identity projects. Finally, it was observed how the form and structure of the novel dialogue and reinforce the fragmentation of the narrative voice, social ties, space and time through ruptures, lack of linearity, citations and generic hybridism of the narrative construction. Finally, the research portrays that the characters Morel, in the narrative foreground, and Vilela, in the narrative background, represent the provisionality and identity fragmentation of the postmodern man. The results show that the novel O caso Morel, by Rubem Fonseca deconstructs, reconstructs and then breaks with the very structure of the text, exposing that postmodern fiction aims to problematize the reference, which results in the weakening of meanings, in the fragmentation of poetics and in identity fragmentation.